The Internationalization Process of Mature Danish Small and Medium-Sized Enterprises: A Qualitative Study - Malene Myhre (Copenhagen Business School (CBS), 2017)
Small and medium-sized enterprises (SMEs) are important to growth, economic development, and job creation in many nations, and especially in small countries like Denmark. According to Statistics Denmark, there are roughly 300,000 active companies in Denmark. Of these, 99.4% are classified as SMEs. International trade is important for small countries, where the economy as a rule is closely integrated (both economically and financially) with the rest of the world. Despite the recognized importance, there is little knowledge about how SMEs approach internationalization. In particularly we lack studies of what makes mature enterprises which have predominantly had a domestic orientation decide to internationalize. Through ten case studies in three industries – machinery manufacturing, food distribution, and healthcare – this study qualitatively explores the internationalization process of mature SMEs with respect to pre-entry market research, market (choice) and entry mode. Through a number of semi-structured, in-depth interviews, I examine (a) how SMEs select their market; (b) how they conduct market research, and (c) how they choose their entry mode. The analysis shows two main reasons for internationalization. Proactive SMEs have an ambition to internationalize, while reactive SMEs respond to the environment. As a consequence, there are different internationalization processes for companies that are forced to seek new markets and companies that have an ambition to internationalize. Findings show that the decision to internationalize is often determined by opportunity. In many cases, the choice of a particular market is not a deliberate strategy but the result of an unplanned chance opportunity. Furthermore, the findings reveal that most SMEs have a preference for near markets and that the motivation for internationalization is largely CEO-driven. Another finding is that SMEs find it difficult to obtain knowledge of the market. The case companies studied use various business and social ties to obtain knowledge, but they struggle to gain access to useful assistance and counseling. This proves to be a significant obstacle and forces many companies to engage in a trial and error approach. Without the right tie, for instance an agent or a business partner, the companies are reluctant to commit. Thus an important conclusion of this study is the significance of the concept of an ad hoc or non-committed internationalization process where attempts at foreign market entry are stretched over several years.
hdl:10398/9468
Keywords: 650